To rewrite in exponential form, the equation would be 5^?=625^x. From here, the bases need to be set equal. Since the fourth root of 625 is 5, the new equation becomes 625^1/4=625^x (625^1/4 is the same as the fourth root of 624). Now that the bases are the same, you can just solve for the variables, which become 1/4=x. Hope this helps 🙂

## Answers ( )

5^?=625^x, x=1/4

To rewrite in exponential form, the equation would be 5^?=625^x. From here, the bases need to be set equal. Since the fourth root of 625 is 5, the new equation becomes 625^1/4=625^x (625^1/4 is the same as the fourth root of 624). Now that the bases are the same, you can just solve for the variables, which become 1/4=x. Hope this helps 🙂